A Literature Review on Urban Sprawl in Developed and Developing Countries - T. Renu, Siva Kumar; Syed Hussain, Tuan Pah Rokiah (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
The urban sprawl is the process of a city that evolves from a high density center to form a low density area towards its periphery based on its own phases involving the historical outbreak of a city. The shape, process and effect of a urban sprawl are different. Therefore, studies related to the urban sprawl need to be carried out for each different city, even in the same country. Experience in developed and developing countries suggests that any urban sprawl have a beneficial and bad effect on society and it also poses a problem to the city's management system. Hence, this article is intended to discuss the outcome of a review of a number of literature in relation to the urban sprawl overview globally, and in the context of Malaysia itself.